Comparison of career decision difficulties between nursing freshmen and interns - Ni Putu Wulan Purnama Sari; Made Mahaguna Putra (International Journal of Public Health Science (IJPHS), 2019)
Career selection is one of the most important decisions an individual makes in his life. High career expectation could result in career decision difficulties. This study aimed to compare and analyze the career decision difficulties between nursing freshmen and interns. This cross-sectional study involved 110 and 66 nursing freshmen and interns respectively (n=176) in two private nursing colleges. Career decision difficulties questionnaire was used in data collection. Descriptive statistic and independent sample t test were used in data analysis (α<.05). Results showed that most respondents experienced moderate difficulties in both groups. Overall, there was no significant difference of career decision difficulty found between groups (p=.057), but indecisiveness, dysfunctional myths, lack of knowledge about the process of career decision making, lack of information, lack of information about occupations, lack of information about ways of obtaining additional information, and internal conflicts were significantly different between groups (all p<α). Career decision difficulties occur similarly both in nursing freshmen and interns.